2012
DOI: 10.1270/jsbbs.62.352
|View full text |Cite
|
Sign up to set email alerts
|

DNA profiling of pineapple cultivars in Japan discriminated by SSR markers

Abstract: We developed 18 polymorphic simple sequence repeat (SSR) markers in pineapple (Ananas comosus) by using genomic libraries enriched for GA and CA motifs. The markers were used to genotype 31 pineapple accessions, including seven cultivars and 11 breeding lines from Okinawa Prefecture, 12 foreign accessions and one from a related species. These SSR loci were highly polymorphic: the 31 accessions contained three to seven alleles per locus, with an average of 4.1. The values of expected heterozygosity ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…Similar results were reported by other studies that used DNA marker analysis to classify pineapple cultivars (Kato et al, 2005;Shoda et al, 2012). Collins (1960) showed that whether the outside edge of the leaf is spiny or lack spines is controlled by a single gene.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were reported by other studies that used DNA marker analysis to classify pineapple cultivars (Kato et al, 2005;Shoda et al, 2012). Collins (1960) showed that whether the outside edge of the leaf is spiny or lack spines is controlled by a single gene.…”
Section: Discussionsupporting
confidence: 83%
“…SSRs in expressed sequence tags (EST-SSRs) have been developed to analyze cross-amplification in pineapple at the species, genus, subfamily, and family levels (Wöhrmann and Weising, 2011). SSR markers have also been used to discriminate pineapple cultivars in Japan (Shoda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other infringement cases, DNA profiling methods were developed for the sweet cherry (Prunus avium L.), rush (Juncus effuses L.), kidney beans (Phaseolus vulgaris L.), and adzuki beans (Vigna angularis (Willd.) Ohwi & Ohashi), among others (Shoda et al, 2012). Our results show that it is possible to identify 59 citrus cultivars, local varieties, and selections, including new cultivars recently developed by the citrus breeding program in the national institute of Japan and that are now commercially produced and frequently used as citrus breeding parents in Japan, on the basis of their genotypes by using eight selected CAPS markers.…”
Section: Discussionmentioning
confidence: 65%
“…The International Union for the Protection of New Varieties of Plants (UPOV; http://www.upov.int/index_en.html, June 14, 2016) has provided and promoted effective systems of plant variety protection. For example, UPOV's working group on Biochemical and Molecular Techniques, and DNA-profiling in particular (BMT), has encouraged the use of DNA profiling techniques to protect the rights of plant breeders (Shoda et al, 2012). To help identify citrus cultivars developed in Japan by using DNA-profiling techniques, several research groups have reported the development of DNA markers (Matsuyama et al, 1992;Omura et al, 2004;Ueda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The size of amplified bands was scored using an internal DNA standard (GeneScan-400HD ROX; PE Applied Biosystems) with GeneScan software (PE Applied Biosystems). The parent-offspring relationships of Korean bred pear cultivars were analyzed by comparing the SSR alleles in each cultivars with registrant parents using the MARCO software (Fujii et al unpublished as cited by Shoda et al 2012). Furthermore, to identify minimal number of marker subsets, MinimalMarker software (Fujii et al 2007) was used because that was necessary to distinguish all of the cultivars to find out identical genotypes of the 21 cultivars generated by the 53 SSR markers.…”
Section: Data Analysis and Ssr Genotyping By Ssr Markersmentioning
confidence: 99%